2016
DOI: 10.1159/000453187
|View full text |Cite
|
Sign up to set email alerts
|

MiR-22 may Suppress Fibrogenesis by Targeting TGFβR I in Cardiac Fibroblasts

Abstract: Background/Aims: Cardiac fibrosis after myocardial infarction (MI) has been identified as a key factor in the development of heart failure, but the mechanisms undelying cardiac fibrosis remained unknown. microRNAs (miRNAs) are novel mechanisms leading to fibrotic diseases, including cardiac fibrosis. Previous studies revealed that miR-22 might be a potential target. However, the roles and mechanisms of miR-22 in cardiac fibrosis remained ill defined. The present study thus addressed the impact of miR-22 in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 30 publications
(37 reference statements)
0
40
0
Order By: Relevance
“…Only later, a link between activation of the fetal gene program, miRNAs, and HF development was suggested [160][161][162]. For some solitary miRNAs, a role in pathological cardiac remodeling in animal models was found [160,[163][164][165][166]. Also, in humans, the relationship between miRNAs and cardiac remodeling has been investigated.…”
Section: Looking Beyond Circulating Proteins: Micrornas and Metabolitmentioning
confidence: 99%
“…Only later, a link between activation of the fetal gene program, miRNAs, and HF development was suggested [160][161][162]. For some solitary miRNAs, a role in pathological cardiac remodeling in animal models was found [160,[163][164][165][166]. Also, in humans, the relationship between miRNAs and cardiac remodeling has been investigated.…”
Section: Looking Beyond Circulating Proteins: Micrornas and Metabolitmentioning
confidence: 99%
“…The precise mechanisms responsible for the actions of these inhibitors require further investigation. Further, we evaluated the effects of T16Ainh-A01 and CaCCinh-A01 on the expression of α-SMA, a typical marker of myofibroblasts, which are closely associated with cardiac fibrosis [30,31], and demonstrated that both inhibitors reduced α-SMA expression at the mRNA and protein level. The synthesis and secretion of collagen are the main functions of CFs, which play a pivotal role in the myocardial repair process [32].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Excessive SGK1 expression was observed in lung fibrosis, diabetic nephropathy, glomerulonephritis, experimental nephrotic syndrome, obstructive nephropathy, liver cirrhosis, fibrosing pancreatitis, peritoneal fibrosis, Crohn´s disease and coeliac disease [7, 43, 91, 92]. SGK1 expression is up-regulated by TGFβ [43], a key stimulator of fibrosis [88, 93-98]. TGFß is in part effective through transcription factors Smad2/3 [7], which are degraded by the ubiquitin ligase Nedd4L [7].…”
Section: Sgk1 Sensitive Infammation and Fbrosismentioning
confidence: 99%